The Performance Comparison of Battery Charging Using MPPT and PWM Controllers on Amorphous Solar Panel-Based E-Scooters - Asrori, Asrori; Adiwidodo, Satworo; Faizal, Elka; Martawati, Mira Esculenta; Mardyansyah, AA (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2024)
Solar Panel-Based Electric Scooter (E-Scooter) is an electric vehicle in the form of a scooter that uses solar panels as a source of electrical energy for charging batteries and a BLDC motor as a wheel drive. With the development of the E-Scooter, it is necessary to know how to charge the battery. The purpose of this research is to determine the type of Solar Charge Controller (SCC) that can maximize battery charging on the E-Scooter. The research method is to compare SCC MPPT and SCC PWM. The research was conducted by monitoring the output current and voltage of the solar charger controller generated by the solar panels every 10 minutes. After that the recorded data will be stored in the monitoring device's storage memory for further processing. The results of the data that have been obtained on the e-scooter using the SCC MPPT type are capable of producing a power of 9.05 W with a current value of 0.33 A and a voltage of 27.47 V. Meanwhile, the PWM type SCC is capable of producing 8.22 W of power with a current value of 0.30 A and a voltage of 27.42 V. So that the MPPT type SCC is more economical than PWM for charging when the e-scooter is not moving. For the running conditions of the MPPT type SCC e-scooter is capable of producing 7.36 W of power with a current value of 0.27 A and a voltage of 27.26 V. Meanwhile, the PWM type SCC is capable of producing a current of 6.81 W with a value of 0.25 A and a voltage 27.24 V. So that the MPPT type SCC is more efficient than PWM for charging when the e-scooter is running.